1999
DOI: 10.1093/jac/43.4.597
|View full text |Cite
|
Sign up to set email alerts
|

Fungal infection and liposomal amphotericin B (AmBisome) therapy in liver transplantation: a 2 year review

Abstract: We reviewed the use of liposomal amphotericin B in 30 patients receiving therapy following liver transplantation over a 2 year period. Five of these patients were treated for presumed invasive aspergillosis: four of them died despite therapy, each having combined renal and respiratory failure at the time of diagnosis of presumed aspergillosis. Post-mortem examination of three of these patients confirmed the diagnosis of aspergillosis. Twenty-five patients were treated empirically; 11 died and supportive eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 11 publications
0
25
0
2
Order By: Relevance
“…Postmortem studies of liver transplant recipients have shown that IFI is often cryptic during life, and that invasive disseminated infection with Aspergillus species is frequently persistent despite prolonged HD therapy with amphotericin B. 2,6,8,26,27,30,31 We recently reviewed our use of AmBisome in 30 patients post-OLT. 31 Of 5 patients administered AmBisome (median dosage, 3.2 mg/k/d; range, 2.8 to 3.5 mg/kg/d for a median of 14 days; range, 6 to 20 days) for presumed invasive aspergillosis, 4 patients died.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postmortem studies of liver transplant recipients have shown that IFI is often cryptic during life, and that invasive disseminated infection with Aspergillus species is frequently persistent despite prolonged HD therapy with amphotericin B. 2,6,8,26,27,30,31 We recently reviewed our use of AmBisome in 30 patients post-OLT. 31 Of 5 patients administered AmBisome (median dosage, 3.2 mg/k/d; range, 2.8 to 3.5 mg/kg/d for a median of 14 days; range, 6 to 20 days) for presumed invasive aspergillosis, 4 patients died.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,8,26,27,30,31 We recently reviewed our use of AmBisome in 30 patients post-OLT. 31 Of 5 patients administered AmBisome (median dosage, 3.2 mg/k/d; range, 2.8 to 3.5 mg/kg/d for a median of 14 days; range, 6 to 20 days) for presumed invasive aspergillosis, 4 patients died. Postmortem examination was performed in 3 of these 4 patients, and invasive aspergillosis was confirmed in each case.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Fisher et al (1999), seis destes pacientes com insuficiência renal e respiratória morreram e a análise tecidual post-mortem revelou Aspergillus spp. em 3 dos casos.…”
Section: Estudos Em Humanosunclassified
“…간이식수술 후 이식거부 반응을 막기 위해 모든 환자에서 면역억제 제를 광범위하게 사용하기 때문에 이식수술 후에는 면역 력이 낮아져 진균 감염의 가능성이 수술 전보다 높아지 게 된다 (6)(7)(8). 간이식수술을 받은 환자에게 있어서 진균 감염에 대한 치료 및 예방은 매우 중요하다 (9). 간이식 후 침습성 아스페르길루스증의 유병률은 약 1.5%로 알려져 있다 (4,(10)(11)(12).…”
Section: 서 론unclassified